2007
DOI: 10.1016/j.jcrs.2006.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Artisan iris-fixated toric phakic and aphakic intraocular lens implantation for the correction of astigmatic refractive error after radial keratotomy

Abstract: We report 2 patients who had radial keratotomy (RK) to correct myopia. The first patient developed a postoperative hyperopic shift and cataract. Nine years post RK, she had intracapsular cataract extraction and implantation of an Artisan aphakic intraocular lens (IOL). Twenty years post RK, hyperopia and astigmatism progressed to +7.0 -5.75 x 100 with a best corrected visual acuity (BCVA) of 20/20. Due to contact lens intolerance, the Artisan aphakic IOL was exchanged for an Artisan toric aphakic IOL. Three mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…However, the rigid Artisan toric pIOL has been extensively studied. [3][4][5][6][7][8][9][10][11][12][13][14] In a European multicenter clinical study, Dick et al 4 found no loss of CDVA and a gain of 1 or more lines from the preoperative CDVA in 65.7% of eyes; in 88.6% of eyes, the UDVA was 20/40 or better. The spherical and astigmatic errors were significantly reduced in all cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the rigid Artisan toric pIOL has been extensively studied. [3][4][5][6][7][8][9][10][11][12][13][14] In a European multicenter clinical study, Dick et al 4 found no loss of CDVA and a gain of 1 or more lines from the preoperative CDVA in 65.7% of eyes; in 88.6% of eyes, the UDVA was 20/40 or better. The spherical and astigmatic errors were significantly reduced in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…This pIOL has been implanted in eyes with keratoconus, 11 after keratoplasty, 12,13 after radial keratotomy, 14 and combined with excimer laser procedures. 15 However, surgically induced astigmatism (SIA) remains a concern when using the rigid Artisan toric pIOL because it is implanted through a large corneal incision.…”
mentioning
confidence: 99%
“…In a recent report, implantation of iris-supported toric pIOLs helped manage the residual myopic astigmatism after RK, although the enhancement ablation was difficult because of a theoretical risk for keratectasia. 10 Pesando et al 4 report the long-term safety, efficacy, accuracy, and predictability of hyperopic ICL implantation in a study of 59 eyes, including 3 eyes with progressive hyperopia after RK; however, the individual outcomes of post-RK eyes are not mentioned. Because toric hyperopic ICLs are not currently available, we selected a spherical ICL for hyperopia in this case.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Despite satisfactory results with monofocal IOLs, the literature on the use of advanced IOL options in post-RK patients is limited. Recently, Tahzib et al 9 reported implantation of an Artisan toric phakic IOL and an aphakic IOL (Ophtec BV) in 2 patients with a history of RK. Similarly, Gupta et al 10 reported 2 cases in which patients with a history of RK had implantation of a multifocal IOL in the nondominant eye and a monofocal IOL in the dominant eye.…”
Section: Jcrs Online Case Reports 2014; 2:73-77 Q 2014 Ascrs and Escrsmentioning
confidence: 99%